Analisis Penerapan Akuntansi Pajak Pertambahan Nilai (PPN) Pada PT. Cahaya Murni Indolampung: (Studi Kasus Pada PT. Cahaya Murni Indolampung (Cahaya Buana Group)) - Alexandra Amadea Christie; Syamsu Rizal (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The aim of this research was to find out how the Value Added Tax (VAT) calculation, collection, recording, and reporting at PT. Cahaya Murni Indolampung, as well as the suitability of applying the Value Added Tax (VAT) accounting at PT. Cahaya Murni Indolampung with the Law No. 42 Years 2009. The research approach used is exploratory research. The types of data taken to support the research variables are qualitative and quantitative data, and the data sources needed are primary and secondary data. Data collection techniques in this study were interviews, observation, and documentation. The data analysis technique applied is descriptive method. The research results showed that PT. Cahaya Murni Indolampung had implemented the calculation, collection, recording, payment of Value Added Tax (VAT) in accordance with the Law No. 42 Years 2009. Meanwhile for VAT reporting, PT. Cahaya Murni Indolampung experienced a delay in reporting Value Added Tax (VAT).